Risk factors of dental disease in working age population of a large industrial city - V. I. Klimenko; I. V. Smirnova (Zaporožskij Medicinskij Žurnal)
Back in 2005, the WHO has identified European targets by 2020, that provide specific measures for improving dental health and define clear rates of intensity and prevalence of dental diseases. Most EU countries that adopted the WHO recommended principles have already achieved the goals regarding dental health. Level of diseases of the teeth and oral cavity among the population of Ukraine is higher than in the EU countries. Consistently high prevalence of dental diseases among population of all age groups, especially prevalence of dental caries, which is confirmed by the results of various epidemiological studies is a cause of concern. Nowadays factors that influence occurrence of the teeth and oral cavity diseases among the working age population of a large industrial city are not enough studied.